Penetrating the barriers - Green, Douglas O N (CCS GeorgetownGY, 1994)
Identifies two steps that must be taken to achieve a state of cultural harmony. Focuses on the possible goods and services we have to offer in the region e.g. music, food, art and craft. Sees cultural tourism as one way of developing our local economies.